How do you solve the following function question?

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

If f(1) = 3 and f(n) = -2f(n-1) + 1 then f(5) will equal what

Jun 9th, 2015

Thank you for the opportunity to help you with your question!

From f(n) = -2f(n-1) + 1 you get that f(2)=-2f(1) + 1=-2*3+1=-5

f(3)=-2f(2) + 1=-2*(-5)+1=11

f(4)=-2f(3) + 1=-2*11+1=-21

And Finally f(5)=-2f(4) + 1=-2*(-21)+1=43

f(5)=43

Please let me know if you need any clarification. I'm always happy to answer your questions.
Jun 9th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jun 9th, 2015
...
Jun 9th, 2015
Sep 20th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer